Introducing Canada to Urban Planning? Henry Vivian’s Canadian Planning Tour, 1910 - Ulmer, Catherine (Urban History Review / Revue d'histoire urbaine, 2018)
From the late nineteenth century onwards, an informal but dedicated group of middle- and upper-class Canadians came to embrace urban planning, building networks across the growing international movement that they used to import and circulate foreign innovations within Canada. This article studies the impact of such transnational planning exchanges through exploring British Garden City planning expert Henry Vivian’s 1910 tour of Canada. Arriving at the request of Earl Grey, Canada’s ninth governor general and an influential planning advocate, Vivian spent three months touring municipalities, lecturing on the Garden City approach, and advising on local urban issues. The article studies the wider Canadian and transnational planning movements from which Vivian’s tour emerged before considering the tour itself and Vivian’s ultimate influence on Canada’s planning movement.